Pengaruh proses pembelajaran Pendidikan Kewarganegaraan dan pendidikan interventif terhadap karakter warga negara muda - Ida Rohayani; Achmad Kosasih Dzahiri; Sapriya Sapriya (Universitas Negeri Yogyakarta, 2010)
This article is based on a research on “the Influence of Civic Education Learning Process and Interventive Education to Young People Character”. It proposes to support facts and reveal that Civics with respectful, responsible approaches and Interfering Education from their parents can build citizens’character. Young people’s character is as morality to support and maintain the harmonious civilization of human life in society and country. These ideas have the background as follows: The anxiety arises in education that the students’ morale is decreasing. This phenomena comes up in formal, informal, and non formal education. Civic Education learning process with respectful, responsible approaches colaborates with parents’ interference. It is a solution to give a guidance to find out the best students’ character. The citizen character building works more effectively whenever it collaborates with parents’s Interfering education. Supported by good morality and infrastructure, SMAN 3 Bandung is categorized as a good civilizing laboratory to build students’ character. Thus needs teacher professionalism as citizenship educator and supported by a conducive school atmosphere.